Development of a Sinitic Clubroot Differential Set for the Pathotype Classification of Plasmodiophora brassicae - Pang, Wenxing; Liang, Yue; Zhan, Zongxiang; Li, Xiaonan; Piao, Zhongyun (Frontiers in Plant Science, 2020)
Plasmodiophora brassicae, which is known for its broad genetic diversity for virulence, is the causal agent of clubroot disease of Brassica crops worldwide. Studies on pathotype characterization with four differential hosts according to Williams’ classification system showed the predominance of pathotype 4 in China. However, the genetic variability within pathotype 4 complicates the breeding of durable clubroot-resistant (CR) cultivars. Herein, a Sinitic clubroot differential (SCD) set was developed using a set of eight differential inbred lines of Chinese cabbage with known or novel CR genes. The presence of immense diversity within pathotype 4 of Williams’ system was verified, and 11 pathotypes were characterized using the developed SCD system. The scalability and practicability of the system was further confirmed with a subset of 95 field isolates from different Brassica crops and different regions of China and Korea. Sixteen pathotypes were detected from 132 field isolates, named Pb1 to Pb16, respectively. Among them, Pb1 and Pb4 were prevalent in diverse Brassica crops in the southern and northern regions of China. Pb12, Pb13, Pb14, and Pb16 showed area-specific distribution. The SCD set developed herein will provide important genetic resources for pathogenicity studies of P. brassicae and for CR breeding in Chinese cabbage and other Brassica crops.